Enhancing Community Knowledge in Managing Waste into Economically Valuable Organic Fertilizer in Manjung Village, Wonogiri - Darnoto, Sri; Jumadi; Santhyami; Anna, Alif Noor; Astuti, Dwi; Rudiyanto; Arini, Maya Intan (Journal of Community Services and Engagement: Voice of Community (VOC), 2025)
Manjung Village, Wonogiri, has been facing serious challenges in waste management with increasing levels of environmental pollution due to a lack of knowledge of effective waste management. Existing organic waste has not been managed properly, resulting in negative impacts on public health and the environment and has no economic value. This activity aims to provide training to partners in managing organic waste in Manjung Village, Wonogiri District, into economically valuable organic fertilizer products. The partner of this activity is the “Manjung Berkah Waste Bank Group” in Manjung Village, Wonogiri District, Wonogiri Regency. Manjung Berkah Waste Bank was used as an activity partner because: (1) it already has waste management management, (2) existing human resources have not been able to manage organic waste optimally, and (3) the partner is one of the Waste Bank pilot institutions that is still active in Wonogiri Regency. The methods used include socialization, mentoring, and training activities. The results of this activity showed a significant increase in participants' knowledge and skills, as evidenced by the comparison of pre-test and post-test results. The increase showed that the training was effective. In addition, the partners also managed to produce organic fertilizer from previously unutilized waste. This activity not only increases environmental awareness but also opens up new economic opportunities for the community.